THE EFFECT OF DIFFERENT SALT CONCENTRATION ON THE QUALITY SALT-FERMENTED (PEDA) MACKEREL (Rastrelliger kanaguarta) - Astria, Novi; Leksono, Tjipto; Iriani, Dian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPeda (salt-fermented fish) is one of the wellknown fishery products in Indonesia. Salt is used to control bacteria life. The fish that is usually used for raw material is a kind of mackerel (Rastrelliger sp.). This research was held to find out the effect of different salt concentration given to the quality of peda (salt-fermented fish) mackerel. Samples were taken from West Sumatera and landed at the Laboratory of Fish Processing Technology, Faculty of Fishery and Marine Science, Riau University, Pekanbaru. Each sample weighing about 200-250 grams. At the laboratory, samples were grouped into two, gutted and ungutted. After cleaned, the fishes were salted in a plastic bucket with four concentration of salt (15%, 20%, 25%, 30%) for 7 days. Then, the fishes were cleaned from salt residue and checked for sensory (appearance, texture, taste, odor), chemical (pH, water activity), and microbiological ( Total Halophilic). The result has shown that the best treatment was in the gutted fish of 20% salt concentration with appearance (whole, cleanly, bright), odor (almost neutral and bit annoying), flavor (really good, specific, there is no another annoying flavor), pH 6.25, water activity 0.77, and total halophilic 9.8 x 104 CFU/gram. Meanwhile, the best texture was found in 25% of salt concentration with specific criteria solid, elastic, and dry enough.Keywords: Peda, mackerel, gutted, ungutted, salt concentration, quality